2017
DOI: 10.1159/000452960
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of <b><i>Streptococcus mutan</i></b>s Growth and Biofilm Formation by Probiotics in vitro

Abstract: To exert anticaries effects, probiotics are described to inhibit growth and biofilm formation of cariogenic bacteria such as Streptococcus mutans (SM). We screened 8 probiotics and assessed how SM growth or biofilm formation inhibition affects cariogenicity of probiotic-SM mixed-species biofilms in vitro. Growth inhibition was assessed by cocultivating probiotics and 2 SM strains (ATCC 20532/25175) on agar. Probiotics were either precultured before SM cultivation (exclusion), or SM precultured prior to probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…1,31 The most common probiotics strains used in oral health belong to the genera Bifidobacterium and Lactobacillus. 20,30,[32][33][34] For instance, when incorporated to commercial toothpastes, L. casei and L. acidophilus were able to in vitro inhibit Candida albicans and Streptococcus salivarius growth. 33 Recently, it has been hypothesized that oral commensals associated with health are likely to be more effective as probiotic species than the traditional gut-associated probiotic species in terms of ability to colonization, health-promoting functions, biocompatibility, and prophylactic dosage.…”
Section: Discussionmentioning
confidence: 99%
“…1,31 The most common probiotics strains used in oral health belong to the genera Bifidobacterium and Lactobacillus. 20,30,[32][33][34] For instance, when incorporated to commercial toothpastes, L. casei and L. acidophilus were able to in vitro inhibit Candida albicans and Streptococcus salivarius growth. 33 Recently, it has been hypothesized that oral commensals associated with health are likely to be more effective as probiotic species than the traditional gut-associated probiotic species in terms of ability to colonization, health-promoting functions, biocompatibility, and prophylactic dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The local anticaries effects may include competitive inhibition with cariogenic bacteria for nutrition or adhesive surfaces [Terai et al, 2015], selective co-aggregation of MS without disturbing other oral flora Lang et al, 2010], and bacteriocin-producing probiotics targeting MS [Burton et al, 2013]. The most commonly used and studied probiotics belong to the Lactobacillus and Bifidobacterium bacterial genera, although not all their strains have the same efficacy in the inhibition of S. mutans growth or biofilm formation [Schwendicke et al, 2017].…”
Section: Probioticsmentioning
confidence: 99%
“…One of the problems identified in using probiotics for caries prevention is that the commonly available Lactobacillus and Bifidobacterium probiotic bacteria are themselves acidogenic and aciduric, and could contribute to the caries process if such bacteria are allowed to colonize the oral cavity [Maltz and Beighton, 2012]. Recent in vitro biofilm studies have confirmed this apprehension with different strains such as Lactobacillus salivarius W24 [Pham et al, 2009], Lactobacillus rhamnosus GG [Schwendicke et al, 2014a], Bifidobacteria animalis lactis BB12 [Schwendicke et al, 2014b], Lactobacillus rhamnosus LB21 [Fernández et al, 2015], and Lactobacillus acidophilus LA-5 [Schwendicke et al, 2017] which have all been shown to lower biofilm pH. In fact, some Lactobacillus and Bifidobacterium strains have greater cariogenic attributes than even MS [Beighton et al, 2010].…”
Section: Probioticsmentioning
confidence: 99%
“…For example, S. salivarius strains can produce bacteriocin-like inhibitory substances with a broad spectrum of activity against cariogenic streptococci including S. mutans. S. oligofermentans is a bacterium that appears to be inversely correlated with the presence of S. mutans within dental plaque samples and was shown to produce hydrogen peroxide with lactic acid as the substrate, leading to the inhibition of S. mutans growth [112,113].…”
Section: Probiotics and Reducing Cariogenic Bacteriamentioning
confidence: 99%